Studi Komparasi terhadap Perlindungan Kepentingan Kreditor dan Debitor dalam Hukum Kepailitan - Siti Anisah (Fakultas Hukum Universitas Islam Indonesia, 2009)
Initially, the goal of bankruptcy law is the liquidation of debitor’s assets. Later, it becomes the means for reorganization of the company’s debitor, and protects the honest individual debitor by executing discharge. The goal is manifested in Acts Number 37 of 2004 which protects the debtor more as the condition of bankruptcy, however it is not easy to get the bankrupt status in reality. That fact was exploited by using the theory of creditor’s bargain and value-based account. This research used normative juridical method and law comparison. The research found that Indonesian Bankruptcy Acts have not so far protected the creditor, debitor and stakeholders; not based on the philosophy of protecting debitor solve; not differentiating the bankruptcy between individual and company though each goal is different. And the last, it has not introduced the discharge for individual bankruptcy.Key word : Bankruptcy law, creditor, debitor